Respuesta :
Answer:
Part 1) [tex]f(x) = 9x- 2[/tex] and [tex]g(x) = -x + 3[/tex]
Find f(g(x)).
[tex]f(x) = 9x- 2[/tex]
Substitute value of g(x) in place of x
[tex]f(g(x)) = 9(-x+3)- 2[/tex]
[tex]f(g(x)) = -9x+27- 2[/tex]
[tex]f(g(x)) = -9x+25[/tex]
So, [tex]f(g(x)) = -9x+25[/tex]
Part 2) [tex]f(x) = 2x + 2[/tex]
[tex]y = 2x + 2[/tex]
Replace y with x and x with y
[tex]x = 2y + 2[/tex]
Find y
[tex]\frac{x-2}{2} = y[/tex]
So, [tex]f^{-1}(x)=\frac{x-2}{2}[/tex]
Substitute x = 4
[tex]f^{-1}(4)=\frac{4-2}{2}[/tex]
[tex]f^{-1}(4)=1[/tex]
Part 3) [tex]f(x) = x + 8[/tex] and [tex]g(x) = x^2- 6x-7[/tex]
[tex]f(x) = x + 8[/tex]
Substitute value of g(x) in place of x
[tex]f(g(x)) =x^2- 6x-7 + 8[/tex]
[tex]f(g(x)) =x^2- 6x+1[/tex]
Substitute x = 2
[tex]f(g(x)) =2^2- 6(2)+1[/tex]
[tex]f(g(x)) =4- 12+1[/tex]
[tex]f(g(x)) =-7[/tex]
Part 4) [tex]f(x) = x^2-8x + 5[/tex]
Substitute x = -1
[tex]f(-1) = (-1)^2-8(-1) + 5[/tex]
[tex]f(-1) =14[/tex]